PEMBENTUKAN DERADIKALISASI PAHAM ISLAM RADIKAL TERHADAP BANGKITNYA TERORISME DI INDONESIA BERDASARKAN PERSPEKTIF KONSTRUKTIVISME - Putri Hergianasari (Universitas Kristen Satya Wacana, 2018)
Terrorisme and radicalism became the contemporary enemy of the Indonesian nation, since the birth of radicalism acts have been around since the decade of the 80s. The emergence of terrorists in Indonesia is driven by a radical ideology. In this paper, radical ideology is driving Islam and it creates radical Islam. Therefore radical Islam is allegedly a forerunner to the growth of acts of terrorism. This paper is analyzed by constructivism theory. The finding said that there is a tendency to change nation’s ideology from Pancasila to Radical Islam. However, in order to eliminate such ideology, the role of the state to counter terrorism must continue to be warner, the strategic agenda that needs to be prepared is total deradicalization, sector reform, reeducation, and massive living culture encouraged. This agenda may not be something new, but the main point is to break the link of radicalism to terrorism by promoting the total deradicalization that begins with the government.